(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
The role of technology is important to consider when working existentially with clients, as technology provides us with the opportunity to expand ourselves without limitations but with implications. The need for the development of the understandings of emerging technologies by the professional will be discussed along with questions and forethoughts.